Penerapan Restorative Justice oleh Pengadilan Negeri Medan untuk Mewujudkan Kepastian Hukum dalam Penyelesaian Tindak Pidana - Nugraha Manuella Meliala; Ismaidar; Muhammad Arif Sahlepi (Dinasti Review Publisher, 2024)
This research aims to evaluate the effectiveness of the implementation of restorative justice by the District Court of Medan in achieving legal certainty for all parties involved in the legal process. The research method used is normative juridical legal research, focusing on written regulations and other legal materials. Data collection is conducted through literature review to explore concepts, theories, or opinions regarding Legal Certainty in the Implementation of Restorative Justice. The analysis is qualitative, explaining the relationship between types of data, selection, and data processing to be systematically outlined. The conclusion of the analysis will include answers to the issues raised and evidence of the truth or falsity of the hypotheses proposed. The results of the research indicate that the Indonesian Criminal Justice System has undergone renewal with the introduction of the concept of restorative justice. This involves perpetrators, victims, and other stakeholders in seeking fair solutions and peace after criminal events. The Public Prosecutor's Office plays a crucial role in prosecution, and the principle of